2019
DOI: 10.1002/app.48287
|View full text |Cite
|
Sign up to set email alerts
|

Coating of polylactide films by chitosan: Comparison of methods

Abstract: Control over biomaterials surface characteristics through surface modification or deposition of coatings is one of the key aspects of tissue engineering. This work was aimed to evaluate an effectiveness of various methods of chitosan-coating formations onto polylactide films using a number of techniques, such as vacuum deposition by electron-beam sputtering, chemical entrapment method, and electrospray procedure. Differently coated films were studied in terms of surface morphology (scanning electron and atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Chitosan is one of the widely used natural polymers for immobilization, because of its biocompatibility, biodegradability, antibacterial activity and its ability to act as a site for binding of other bioactive components or cell attachment [19]. There are a number of works describing various approaches to chitosan immobilization or chitosan-based coating deposition onto hydrophobic polymeric materials [20][21][22][23]. Some of these approaches could be more effective than plasma treatment, but require the application of specific and rather expensive techniques or additional components, which makes plasma treatment the easiest way to achieve surface modification and chitosan immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is one of the widely used natural polymers for immobilization, because of its biocompatibility, biodegradability, antibacterial activity and its ability to act as a site for binding of other bioactive components or cell attachment [19]. There are a number of works describing various approaches to chitosan immobilization or chitosan-based coating deposition onto hydrophobic polymeric materials [20][21][22][23]. Some of these approaches could be more effective than plasma treatment, but require the application of specific and rather expensive techniques or additional components, which makes plasma treatment the easiest way to achieve surface modification and chitosan immobilization.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers are widely used more than ceramic biomaterials [82]. The required mechanical and physical properties, the simplicity of secondary processing stages, the cost, and the ease of manufacturing to manufacture diverse shapes are the major advantages of polymers when compared with metallic and ceramic biomaterials [58][59][60][61][62][63]. The main reasons behind the wide usage of polymers are biocompatibility, biodegradability, sterilizability, adequate mechanical and physical properties, and low melting point, which make them easy to fabricate [64].…”
Section: Polymersmentioning
confidence: 99%
“…They revealed that polymers are widely used more than ceramics and metallic biomaterials. The ease of manufacturing to produce various shapes, ease of secondary processing stages, reasonable cost, and availability with desired physical and mechanical properties are the major advantages of polymers when compared with metallic and ceramic biomaterials [58][59][60][61][62][63]. Devi P et al [64] highlighted the main reasons behind the wide usage of polymers.…”
Section: Introductionmentioning
confidence: 99%